Polymer composite materials with a high level of thermal stability based on phenolic resins and disperse silica fillers - Kabat, O.S.; Kobelchuk, Yu.M.; Chervakov, D.O.; Chervakov, O.V. (Наука, технології, інновації, 2018)
Development of the engineering industry is difficult without using of heat-resistant polymer composite materials for manufacturing of machines and mechanisms parts operating at temperatures up to 300°C. For this purpose it was suggested the diphenylolsulfone formaldehyde resin as a polymer matrix, and different modifications of disperse silicas — white soot WS-120 and aerosol A-380 — were selected for fillers. The developed phenoplasts have high level of thermal stability (up to 370 °C), it’s at 25–30°C is higher, then for initial resins. Apparently, this is a result of increasing of the interaction level on the boundary “polymer-disperse filler”, under the processing condition (at temperatures 170–190°C) due to appearing of covalent and hydrogen bonds between hydroxyl groups at the surface of the silica and methylol groups of the polymer matrix. Розвиток машинобудівної галузі ускладнився без використання термостійких полімерних композиційних матеріалів для деталей машин і механізмів, що працюють при температурах до 300°С. Запропоновано як полімерну матрицю обрати діфенілолсульфон-формальдегідну смолу, а в якості наповнювачів використати дисперсні кремнеземи — білу сажу марки БС-120 та аеросил марки А-380. Розроблені матеріали мають високу термічну стабільність (до 370°C), що на 25-30°C вище, ніж для ненаповненого полімеру. Такий результат проявився при збільшенні рівня взаємодії в процесі переробки на межі розподілу фаз “полімер — дисперсний наповнювач” в умовах переробки (при температурах 170–190°С) за рахунок утворення ковалентних і водневих зв’язків між гідроксильними групами на поверхні наповнювача та метилольними групами полімерної матриці. Развитие машиностроительной отрасли затруднено без использования термостойких полимерных композиционных материалов для изготовления деталей машин и механизмов, работающих при температурах до 300°С. Предложено в качестве полимерной матрицы использовать дифенилолсульфонформальдегидную смолу, а в качестве наполнителей — дисперсные кремнеземы — белую сажу марки БС-120 и аэросил марки А-380. Разработанные материалы имеют высокую термическую стабильность (до 370°C), что на 25-30°C выше, чем для ненаполненного полимера. Такой результат может быть следствием увеличения уровня взаимодействия на границе раздела фаз “полимер — дисперсный наполнитель” в условиях переработки (при температуре 170–190°С) за счет образования ковалентных и водородных связей между гидроксильными группами на поверхности наполнителя и метилольными группами полимерной матрицы.